The illustrated man - Bradbury, Ray, 1920-2012 (Harper Perennial modern classics., 2011)
Classic Bradbury, this collection of tales offers images that are as keen as a tattooist's needle and as colorful as the inks that stain the body. Featuring a new Introduction, "The Illustrated Man" presents 18 startling visions of humankind's destiny, unfolding across a canvas of decorated skin.